Women's Autonomy and Household Health Factors in Infant Mortality - Sunnia Mutia; Asnawi Abdullah; Nopa Arlianti (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2024)
Introduction: Infant mortality remains a significant concern, spanning from national to global contexts. Despite substantial global progress in reducing infant mortality rates, considerable challenges persist, particularly in specific regions. In 2020, 2.4 million infant deaths occurred within the first month of life, underscoring the need for continued attention to this issue. This study aims to identify the influence and risks of women's autonomy and household health characteristics on infant mortality. Objective: The objective of this research is to analyze the impact and risks of women's autonomy, household wealth, maternal education, maternal occupation, delivery method, antenatal care, postnatal care, and birth attendant on infant mortality Method: This study is quantitative in nature, employing a cross-sectional design to examine the influence and risks of sociodemographic factors and household health characteristics on infant mortality. A bivariate and multivariate analysis was conducted on 3,624 respondents. The inclusion criteria were: (a) mothers who were married and living with their husbands, (b) mothers aged 15-49 years, and (c) cases of death of the most recent child from the couple (aged 0-12 months). The exclusion criteria included: (a) divorced mothers, (b) mothers who had never given birth, and (c) mothers younger than 15 years or older than 49 years. Result: The study found no significant associations between women’s autonomy (p=0.499; OR=1.2), household economic status (p=0.09; OR=0.7), delivery method (p=0.856; OR=0.9), quality of antenatal care (p=0.137; OR=1.6), or birth assistance (p=0.277; OR=1.3) and infant mortality. However, significant associations were identified between maternal education (p=0.043; OR=3.1), maternal employment status (p=0.013; OR=0.5), and postnatal care (p=0.0001; OR=5.2) and infant mortality. Conclusion: The study recommends that the healthcare sector prioritize improving the quality and accessibility of antenatal and postnatal care programs. This includes enhanced training for healthcare workers, promoting regular check-ups, and monitoring infant health post-birth.